2022
DOI: 10.3390/oral2040029
|View full text |Cite
|
Sign up to set email alerts
|

Factors Determining the Willingness of Nigerian Clinicians to Recommend Protected Oral Sex: An Online Exploratory Study

Abstract: Oral sex, a risky sexual behaviour, is now a common sexual behaviour in Nigeria. Nigerian clinicians play crucial roles in the promotion of healthy sexual behaviours among the lay public. This study seeks to identify those factors that determine the willingness of Nigerian clinicians to recommend protected oral sex to patients with history of oral sex practice. This study surveyed 330 clinicians in Nigeria, using an e-questionnaire circulated via WhatsApp. The collected data were analysed using SPSS version 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 49 publications
(72 reference statements)
1
12
0
Order By: Relevance
“…This empty review points out several concerns about the commonest oral STDs in Africa. Oral sex is commonly practised among heterosexuals and homosexuals in Africa, 30 , 31 but published interventions on the prevention and care of oral STDs, particularly in the dental care settings, are not available. This shows that oral STDs in Africa is a neglected public health area in Africa.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This empty review points out several concerns about the commonest oral STDs in Africa. Oral sex is commonly practised among heterosexuals and homosexuals in Africa, 30 , 31 but published interventions on the prevention and care of oral STDs, particularly in the dental care settings, are not available. This shows that oral STDs in Africa is a neglected public health area in Africa.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent survey of a sample of dental surgeons in Nigeria, Africa, it was observed that majority of them were unaware of the protective measures that can be used to prevent the transmission of oral STDs during oral sex 30 ; hence, this may be a major factor contributing to the lack of preventative intervention, by DCPs, on oral STDs in Africa. Also, in the survey, 30 it was identified that the practice of educating dental patients on the risks of unprotected oral sex as well as the precautionary measures that can be adopted to ensure safer oral sex was very low among participating dental surgeons. 30 However, in the study, 30 the low practice was attributed to the highly conservative sociocultural landscape on sex‐related issues in Nigeria.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations